2021
DOI: 10.1002/pbc.29362
|View full text |Cite
|
Sign up to set email alerts
|

Comparing efficacy and side effects of two systemic chemotherapy regimens for eye‐preserving therapy in children with retinoblastoma

Abstract: Background: Eye-preserving therapy in retinoblastoma comprises systemic chemotherapy, but studies analyzing the efficacy of different chemotherapy regimens are scarce. Methods:The efficacy and side effects of two different eye-preserving chemotherapy regimens containing either vincristine, etoposide, and carboplatin (VEC) or cyclophosphamide, vincristine, etoposide, and carboplatin (CyVEC) were compared in a prospective non-interventional observational study including children diagnosed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
1

Year Published

2022
2022
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 39 publications
2
5
1
Order By: Relevance
“…This falls in the 40–82% range previously reported [35‒39], although a direct comparison is difficult because of differences in the examined populations and treatment protocols. Regarding eye salvage, Lumbroso-Le Rouic et al [25] found an event-free and an overall eye survival rate of 75% and 78%, respectively, which came in accordance with the findings of a recent German and Austrian study [31]. The 62.5% event-free eye survival rate in patients with group D/E retinoblastoma found by Muhammed et al [27] was higher than previously reported [29, 31], but this could be explained by the shorter follow-up in this study.…”
Section: Discussionsupporting
confidence: 83%
See 3 more Smart Citations
“…This falls in the 40–82% range previously reported [35‒39], although a direct comparison is difficult because of differences in the examined populations and treatment protocols. Regarding eye salvage, Lumbroso-Le Rouic et al [25] found an event-free and an overall eye survival rate of 75% and 78%, respectively, which came in accordance with the findings of a recent German and Austrian study [31]. The 62.5% event-free eye survival rate in patients with group D/E retinoblastoma found by Muhammed et al [27] was higher than previously reported [29, 31], but this could be explained by the shorter follow-up in this study.…”
Section: Discussionsupporting
confidence: 83%
“…Few associations were nominally statistically significant at the p = 0.05 level, and all of them pertained to the comparison between two drug combinations performed by Chawla et al [24]. The VEC protocol, the most used chemotherapeutic protocol for retinoblastoma [12, 13, 31], was associated with lower disease progression and mortality rates as well as less adverse events compared to a 5-drug combination consisting of carboplatin and etoposide, alternating with cyclophosphamide, idarubicin, and vincristine. A further comparison between different protocols showed that etoposide and carboplatin might offer better tumor control than vincristine and carboplatin when used as neoadjuvant chemotherapy, without an increase in severe toxicity [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Long-term results included gain in visual acuity, defined as an improvement of 2 or more lines, local recurrences, development of second primary malignancies (SPM), depending on the treatment modalities, and metastatic disease. Systemic chemotherapy was administered as a combination of vincristine, etoposide, and carboplatin and, in some cases, supplemented by cyclophosphamide, whereby 75% of the patients got more than 5 treatment cycles [8]. The apex dose for brachytherapy with 106 ruthenium plaques was initially selected at 138 Gy, followed by a reduction to 88 Gy at the tumor apex from 2004.…”
Section: Methodsmentioning
confidence: 99%